FORENSIC ACCOUNTING AS A TOOL FOR ACHIEVING THE UNITED NATIONS SUSTAINABLE DEVELOPMENT GOALS (Third Sector Social Economic Review, 2023)
This paper addresses the role forensic accounting plays in achieving the United Nations Sustainable Development Goals. Forensic accounting helps countries tackle various economic, social and environmental challenges by providing transparency, accountability and effective resource management. Forensic accounting provides an important tool for the detection and prevention of financial irregularities and corruption. Sound forensic accounting procedures can be used to improve financial governance, reduce risks and promote sustainable development. The United Nations has set 17 goals, including targets such as poverty reduction, gender equality, climate action and responsible consumption and production. Forensic accounting contributes directly to these goals, uncovering financial discrepancies, identifying illicit financial flows and promoting ethical business practices. In addition, forensic accounting techniques provide valuable information on the effectiveness of policies, programs and projects, enabling progress to be measured and evaluated. Forensic accounting also plays an important role in promoting evidence-based decision making and a culture of accountability. This research highlights the potential for forensic accounting to be a catalyst for achieving goals and emphasizes the need for collaboration to develop standardized practices. By harnessing the power of forensic accounting, stakeholders can strengthen financial integrity and contribute to a more equitable and resilient future by supporting sustainable development.
Keywords: Forensic Accounting; Sustainable Development Goals; Accountability; Corruption; Resource Management